Assessment of Physical Fitness and Training Effect in Individual Sports - Ambrozy, Tadeusz; Ozimek, Mariusz; Ostrowski, Andrzej; Duda, Henryk; Spieszny, Michał (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Physical fitness is the basis for the success of players in sports, and its monitoring makes it possible to assess the effectiveness of training and identify possible errors. During training, thanks to the use of control results, these activities are modified, which better prepares players for competition. This Special Issue, entitled "Assessment of Physical Fitness and the Effect of Training in Individual Sports" presents the results of coaching control and the results of monitoring progression in training, as well as an assessment of the physical fitness of athletes practicing individual sports.